The effect of mirroring approach with visual feedback on pronunciation improvement perception: mediating role of intrinsic motivation and cognitive engagement - Samah Yaslam Saleh Baagbah; Malini Ganapathy (Cogent Education)
The study aims to investigate the direct role of the mirroring approach with visual feedback on learners’ pronunciation improvement. The study also examines the roles of intrinsic motivation, cognitive engagement, and their interrelated relationships with mirroring and visual feedback on learners’ pronunciation improvement. Using Partial Least Squares-Structural Equation Modelling (PLS-SEM) approach, the study employed a cross-sectional design and collected data quantitatively. A total of 120 Arab EFL learners from Saudi Arabia and Yemen participated in a prior intervention and answered a follow-up questionnaire. The results indicated that the mirroring approach with visual feedback has a positive impact on the learners’ pronunciation improvement. Intrinsic motivation and cognitive engagement mediate the relationship between mirroring with visual feedback and pronunciation improvement. This study contributes to pronunciation instruction literature by understanding the interplay between visual feedback, intrinsic motivation, cognitive engagement, and pronunciation improvement. Untangling the intertwined influence of these factors provides practical implications for teachers and curriculum developers to adapt effective pronunciation instructions that are designed based on instructions supported by technology and psychological needs.